2020
DOI: 10.1080/08897077.2019.1635556
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Voluntary Admission and Restraint use after a Comprehensive Tobacco-Free Policy in Inpatient Psychiatric Health Facilities

Abstract: Background: Cardiovascular and respiratory diseases, predominantly due to tobacco use, are the leading causes of death among individuals with serious and persistent mental illness. However, many psychiatric health facilities do not routinely treat tobacco use disorder. The purpose of the current study was to examine the impact of implementing a tobacco-free policy in inpatient psychiatric health facilities in a large, urban setting on behavioral problems, treatment access, and tobacco treatment. Methods: Data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
1
1
0
1
Order By: Relevance
“…Previous studies have reported changes in prescribing of nicotine replacement therapy following smoke-free policies in psychiatric hospitals, although these were simple comparisons done before and after policy implementation that did not account for secular trends, seasonality, or autocorrelation. [15][16][17] Our observation of increased nicotine replacement therapy dispensing is consistent with these studies and findings from the qualitative data collected as part of TIPs, which described extensive preparations across the Scottish Prison Service for increased demand for cessation or abstinence support. 11 The observed decline in dispensing of other medications used to support cessation or abstinence attempts might be explained by multiple factors, including a decline in opportunities to prescribe varenicline for the licensed indication of cessation of tobacco smoking; the increased availability of nicotine replacement therapy, which is recommended as first line in local formularies in Scotland and is substantially cheaper than other medications used to support cessation or abstinence attempts; and widespread availability and uptake of rechargeable e-cigarette devices.…”
Section: Discussionsupporting
confidence: 83%
“…Previous studies have reported changes in prescribing of nicotine replacement therapy following smoke-free policies in psychiatric hospitals, although these were simple comparisons done before and after policy implementation that did not account for secular trends, seasonality, or autocorrelation. [15][16][17] Our observation of increased nicotine replacement therapy dispensing is consistent with these studies and findings from the qualitative data collected as part of TIPs, which described extensive preparations across the Scottish Prison Service for increased demand for cessation or abstinence support. 11 The observed decline in dispensing of other medications used to support cessation or abstinence attempts might be explained by multiple factors, including a decline in opportunities to prescribe varenicline for the licensed indication of cessation of tobacco smoking; the increased availability of nicotine replacement therapy, which is recommended as first line in local formularies in Scotland and is substantially cheaper than other medications used to support cessation or abstinence attempts; and widespread availability and uptake of rechargeable e-cigarette devices.…”
Section: Discussionsupporting
confidence: 83%
“…Diversos estudios mostraron que después de la restricción de fumar, en los servicios de psiquiatría, la salud mental de los pacientes psiquiátricos fue mejorada, disminuyendo la probabilidad de una nueva internación. Además de eso, existen evidencias de que la prohibición de fumar no es acompañada del aumento de la agresividad de los pacientes, mostrando que su implementación es más fácil de lo que inicialmente se imaginaba (21)(22)(23)(24)(25)(26) .…”
Section: Discussionunclassified
“…The lack of change in screening rates may be explained because the screening rates at 2015 were already quite high (i.e., 93%) and the NL-TTS could not further affect these rates because of a plateau effect. Nevertheless, implementing tobacco-free policies and increasing the availability of tobacco treatment resources can reduce tobacco use among patients (Scheeres et al, 2020). Therefore, implementing systems that support nurses and other health care providers in providing tobacco treatment within psychiatric settings is important to enhance conscientious psychiatric care.…”
Section: Discussionmentioning
confidence: 99%